Diversity Policies as Tools to Increase Participation and Encounters. - Nyseth, Torill (Nordic Journal of Migration Research, 2021)
Informed by the concept of diversity, this article discusses the issue of municipalities’ facilitation of ethnic diversity and integration in two cities in northern Norway. Municipalities are in a position to accommodate ethnic diversity in more pragmatic ways than the nation-state through local policies. We explore diversity policies in three different areas: democratic participation, urban planning, and cultural policies. The study finds ambivalences in the involvement of immigrants in urban planning processes and to some degree indifference in planning for diversity but also real attempts at recognition by giving immigrants a voice in local politics.